Humpty Dumpty climbs again - Horowitz, Dave, 1970- (New York, NY : G.P. Putnam's Sons, 2008)
Humpty Dumpty has not climbed a single wall since his great fall, despite the urging of friends and teasing of others, but when one of the king's horses is stuck he finds the courage--and the proper climbing equipment--to help out.
A Junior Library Guild selection
Keywords: Courage -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Rock climbing -- Juvenile fiction; Stories in rhyme; Courage -- Fiction; Characters in literature -- Fiction; Rock climbing -- Fiction; Humorous stories